The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18356/31c71be8-en
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fiscal decentralization on growth, inflation and inequality in the Americas

Abstract: This paper analyses the impact of fiscal decentralization on economic growth, inflation and Gini coefficients in 12 countries of the Americas. The findings suggest that the positive impact of this process has been more modest than anticipated, with revenue decentralization having a detrimental effect on economic growth and expenditure decentralization a positive one in developing nations of the Americas. Regarding the impact on income inequality, the results indicate that fiscal decentralization can play an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…Switzerland's historically grown internal economic complexity, its decentralized system of governance and its high rates of migration may have crucially contributed to its global economic competitiveness as well as its good performance in social and environmental terms. Even though recent empirical research on the impact of decentralized political systems on social inequality has shown rather mixed results in countries such as the USA [32], the Americas [33] and China [34], the degree of social inequality in the federal system of Switzerland remains comparatively low [22]. However, since Switzerland has not changed its federal system in any substantial form since its foundation in 1848, and its economy was less affected by the two World Wars than in the rest of Europe, it is difficult to investigate how social equality would have fared under different circumstances.…”
Section: Economic Complexity and Migration In Switzerlandmentioning
confidence: 99%
“…Switzerland's historically grown internal economic complexity, its decentralized system of governance and its high rates of migration may have crucially contributed to its global economic competitiveness as well as its good performance in social and environmental terms. Even though recent empirical research on the impact of decentralized political systems on social inequality has shown rather mixed results in countries such as the USA [32], the Americas [33] and China [34], the degree of social inequality in the federal system of Switzerland remains comparatively low [22]. However, since Switzerland has not changed its federal system in any substantial form since its foundation in 1848, and its economy was less affected by the two World Wars than in the rest of Europe, it is difficult to investigate how social equality would have fared under different circumstances.…”
Section: Economic Complexity and Migration In Switzerlandmentioning
confidence: 99%
“…In this sense, we should bear in mind that one of the most reliable reasons for having yet inconclusive empirical evidence is because researchers rely mostly on the data provided by the GFS of the IMF on revenue and expenditure decentralization but we are aware of the fact that such data do not always give us the actual degree of fiscal autonomy reached by the subnational governments (Bojanic, 2018;Ebel & Yilmaz, 2002;Martinez-Vazquez et al, 2016;Stegarescu, 2005). This is so because, theoretically, tax sharing and other tax decentralization formulas do not provide real tax autonomy (Lago-Peñas et al, 2017).…”
Section: Revenue and Expenditure Decentralizationmentioning
confidence: 99%
“…Despite Rodden (2004) complains regarding the standard formula to measure fiscal decentralization by the shares of subnational revenues and/or subnational expenditure to general government, most recent research, even for OECD countries (Bojanic, 2018;Makreshanska-Mladenovska & Petrevski, 2019), keep relying on the shares of subnational governments revenue/expenditure to general government revenue/expenditure. In this article, for our data set of developing federations, such sophisticated decentralization indicators were not possible to have access to and we rely on two measures of fiscal decentralization based on the IMF data, as explained in section "Data and Method.…”
Section: Revenue and Expenditure Decentralizationmentioning
confidence: 99%
“…According to [23], three main themes from the viewpoint of fiscal decentralization have been explored in the economics literature. The first concerns how governance is affected by the transfer of revenue and spending powers to regional institutions [24].…”
Section: Definition Of Fiscal Decentralizationmentioning
confidence: 99%